Herbal Leaf Tea as an Economic and Health Potential of the Suci Village Community, Panti – Jember - Dwinianti, Edia; Setyati, Dwi; Rosida, Waki'atil; Mustafidah, Qori'atul; Su'udi, Mukhamad (Jurnal Inovasi Sains dan Teknologi untuk Masyarakat, 2025)
The community in Suci Village, Panti Jember has recognized and cultivated family medicinal plants (TOGA) to provide traditional medicine because of its distance from the city center, limited health facilities and pharmacies. The utilization of TOGA is still limited as herbal medicine through liquid herbal medicine which is less practical and has a short shelf life, so it is necessary to carry out mentoring activities in the development of TOGA for herbal tea leaves. This activity aims to empower the community in Suci Village in optimizing the potential and utilization of local biodiversity as an ingredient for leaf herbal tea. The method of activity implementation included lectures, hands-on practice of making herbal tea leaves and discussions. The Biology lecturer team at the University of Jember introduced the local potential, health benefits of herbal tea leaves, and the production process from washing, drying, packaging, to marketing. The results of this activity showed that the socialization of the potential, benefits and production of herbal tea leaves increased community knowledge by 84% in the utilization of local plants for health and economic potential. In addition, interactive discussions generated additional ideas such as the utilization of beluntas leaves and coffee peels as herbal tea ingredients, as both ingredients are available in Suci Village and have not been optimally utilized. Through this activity, it is hoped that the community in Suci village will be able to develop herbal tea through the utilization of local potential that has health benefits and economic potential through environmentally friendly products.